THE POWER OF THE SANAD NETWORK AND ISLAMIC DISCOURSE IN THE ARBA'IN HADITH MANUSCRIPTS OF NUSANTARA SCHOLARS (RIWAYAH, 2022)
Islam Nusantara was introduced as a response to the issue of radicalism and terrorism that was emerging on the international stage. The pesantren-style education model, which focuses entirely on studying the kitab kuning (turats), is considered effective in addressing this issue. The kitab kuning serves as an effective medium for promoting religious moderation within the socio-cultural context of Muslims in the Nusantara. One approach is by exploring the manuscript heritage written by Nusantara scholars. This paper examines Arba’in hadith manuscripts written by Nusantara scholars, namely the works of Mahfuzh al-Tarmasi, Hasyim Asy’ari, Nawawi al-Bantani, and Yasin al-Fadani, from the 17th to the 20th century. Using a philological approach, the findings of this study show that these books were written in the context of Indonesia’s colonial period and aimed to provide a counter-narrative to religious orthodoxy. The Islamic discourse embedded in these works relates to: 1) Morality, which encourages a moderate attitude towards everyone, all creatures on earth, even towards enemies; 2) Religious moderation, by considering those of different faiths as brothers; 3) Work discipline, aimed at fostering the spirit of striving for a decent life; 4) The concepts of sunnah and bid’ah are explained to provide a counter-narrative to the Wahhabi-style religious discourse that attacks local traditions. Furthermore, at roughly the same time, Muslims in Haramain took a stricter stance toward tradition and sought to return religion solely to the Qur'an and Hadith, while Muslims in the Nusantara were more receptive to local traditions. This is evidenced by the incorporation of local contexts into Arba’in hadith works, such as the emphasis on mutual compassion in the context of Dutch colonialism. This represents the scholarly independence of hadith studies developed by Nusantara hadith scholars.Kuasa Jaringan Sanad dan Diskursus Keislaman dalam Naskah Hadis Arba’in Ulama Nusantara. Islam Nusantara diperkenalkan sebagai respon atas isu radikalisme dan terorisme yang sedang mencuat di kancah internasional. Model pendidikan ala pesantren yang tertumpu penuh pada pengkajian kitab kuning (turats) dinilai efektif untuk membendung isu tersebut. Kitab kuning menjadi media yang efektif untuk melakukan gerakan moderasi beragama dalam konteks sosio-kultural umat Islam di Nusantara. Salah satunya dengan menggali khazanah manuskrip yang ditulis oleh ulama Nusantara. Tulisan ini mengkaji naskah-naskah hadis Arba’in yang ditulis oleh ulama Nusantara, yakni karya Syaikh Mahfuzh al-Tarmasi, karya Syaikh Hasyim Asy’ari, karya Syaikh Nawawi al-Bantani, dan karya Syaikh Yasin al-Fadani, pada abad ke-17 hingga ke-20. Dengan pendekatan filologi, temuan dari penelitian ini menunjukkan bahwa kitab-kitab tersebut ditulis dalam konteks penjajahan Indonesia sekaligus bertujuan untuk kontra narasi terhadap ortodoksi beragama. Diskursus keislaman yang ditanamkan adalah berkaitan dengan; 1) Moralitas yang mengarah pada upaya moderasi sikap terhadap siapapun, seluruh makhluk di muka bumi, sekalipun terhadap musuh. 2) Moderasi beragama dengan cara menganggap saudara kepada mereka yang tidak seiman. 3) Kedisiplinan dalam bekerja ditujukan untuk menumbuhkan semangat perjuangan mendapatkan kehidupan yang layak. 4) sunnah dan bid’ah dijelaskan untuk memberikan kontra narasi terhadap wacana keagamaan ala Wahabisme yang menyerang tradisi-tradisi lokal. Selanjutnya, dalam waktu yang relatif bersamaan, Muslim di Haramain lebih keras terhadap tradisi dan mencoba mengembalikan agama kepada al-Qur’an dan hadis an sich, sementara Muslim di Nusantara lebih ramah terhadap tradisi lokal. Terbukti memasukkan konteks lokalitas dalam penyusunan karya hadis Arba’in, seperti saling mengasihi kepada sesama dalam konteks penjajahan Belanda. Inilah bentuk independensi keilmuan hadis yang dimiliki oleh ulama hadis di Nusantara.